Redundancy Elimination in DTN via ACK Mechanism - Zhang, Xiqing; Feng, Yuan; Hong, Feng; Guo, Zhongwen (EAI Endorsed Transactions on Security and Safety, 2015)
The traditional routing protocols for delay tolerant networks (DTN) usually take the strategy of spreading multiple copies of one message to the networks. When one copy reaches destination, the transmission of other copies not only waste the bandwidth but also deprive other messages of the opportunities for transmission. This paper brings up a mechanism to eliminate the redundant copies. By adding an acknowledge field to the packet header to delete redundant copies, it can degrade the network overhead while improve the delivery ratio. Simulation results confirm that the proposed method can improve the performance of epidemic and Spray and Wait routing protocol.